The Criminal Law Policies in Law Enforcement of Local Regulations on Smoking-Free Areas - Dian Pramythasari Utamawati; Gunarto Gunarto (Law Development Journal, 2021)
The purpose of this research is as follows: To know and analyze criminal law policy in enforcing local regulations on No Smoking Areas. To find out and analyze the implementation in enforcement of local regulations on No Smoking Areas. To find out and analyzebarriers to implementing the enforcement of local regulations on No Smoking Areas and their solutions. This study uses an empirical juridical approach, with descriptive analytical research specifications. The data used in this study are secondary data obtained through library research and primary data which are then analyzed qualitatively. The result of this research is that the purpose of this policy is to provide human rights for citizens to obtain a clean, healthy and safe environment. Implementation in the Enforcement of Regional Regulations on No Smoking Areas is still not optimal as seen from the previous discussion there are still individuals or employees who have not complied with the regional regulations for no smoking areas. Barriers: a. A designated smoking area that is rarely used. b. Lack of employee awareness of comfort and health. c. There are still employees who have not complied with these regulations. The solution: a. The person in charge again provides outreach on the No Smoking Area Regional Regulation to employees. b. Provide sanctions in the form of fines. c. Improve communication about smoking rooms. d. Raise employees' awareness of the benefits of smoke-free areas.